2009
DOI: 10.1103/physrevb.79.060410
|View full text |Cite
|
Sign up to set email alerts
|

Theory of microwave superradiance from a Bose-Einstein condensate of magnons

Abstract: We show that the nearly uniform mode generated by the confluence of Bose-Einstein condensate ͑BEC͒ magnon pairs produced by microwave radiation in a film of yttrium iron garnet ͑YIG͒ is a coherent magnon state. This state corresponds to a macroscopic precessing magnetization which emits a superradiant microwave signal as a result of the cooperative action of the spins. The theory explains quantitatively recent experimental observations of microwave emission from a BEC of magnons in a YIG film when the driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…Moreover, Φ(t) ensures the normalization of the probability distributions, and plays the role of the logarithm of a nonequilibrium partition function: Φ(t) = lnZ(t). It is verified that 4) and similarly for the other quantities, in complete analogy with the situation in equilibrium, meaning that F q (t) and the others in set (15) are the nonequilibrium thermodynamic variables said conjugated to the basic variables in set (16). Furthermore, it is verified that…”
Section: Appendix B the Nonequilibrium Statistical Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Φ(t) ensures the normalization of the probability distributions, and plays the role of the logarithm of a nonequilibrium partition function: Φ(t) = lnZ(t). It is verified that 4) and similarly for the other quantities, in complete analogy with the situation in equilibrium, meaning that F q (t) and the others in set (15) are the nonequilibrium thermodynamic variables said conjugated to the basic variables in set (16). Furthermore, it is verified that…”
Section: Appendix B the Nonequilibrium Statistical Operatormentioning
confidence: 99%
“…It can be shown that 13) and the (acoustic) magnon dispersion relation is given by 14) and Refs. [4,67] presents recent studies on this dispersion relation in cases of thin films of YIG.…”
Section: Appendix a The Hamiltonian Of The Magnon Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, a lot of progress has been made for BEC of magnons and exciton-polaritons [13][14][15][16][17][18][19]. Although the observation of Bose-Einstein condensation of photons is more recent, it has also motivated theoretical studies: Klaers et al predicted a regime of large fluctuations of the condensate number [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the narrowing of the magnon distribution with respect to that determined by the classical Boltzmann statistics is more than six orders of magnitude! The detailed theory of BEC of interacting quasi-particles with a finite lifetime is still missing [12][13][14][15][16]. However, one can imagine that, owing to a finite lifetime of the particles, each quantum state is spread in frequency, the width of the spreading df being determined by the lifetime, t 0 : df ≈ (2pt 0 ) −1 .…”
Section: Bose-einstein Condensationmentioning
confidence: 99%